Pengaplikasian AI Video Editing Autopod Terhadap Efektifitas Produksi & Estetika Visual - SUBADI, SUBADI (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2024)
The media industry faces various challenges, technological developments and market disruptions, causing traditional media companies to experience a decline in advertising revenue and mass layoffs. To remain competitive and overcome these challenges, media companies are beginning to adapt to various strategies, including artificial intelligence ). Now artificial intelligence is starting to be used in various aspects of video content creation, such as for video editing under the name Autopod. With maximum use of AI, media companies can streamline time and operational costs. The research method used is qualitative with a participatory approach. This approach aims to develop a more profound and holistic understanding of the experiences and views of researchers who focus on discussing the adaptation and application of AI in the video editing process and its visual aesthetic needs.